Asteroseismological analysis of the GW Virginis stars SDSS J0349-0059 and VV 47 - Calcaferro, Leila Magdalena (2017)
We present an asteroseismological analysis of the GW Vir stars SDSS J0349-0059 and VV47. We found good agreement between our mass determinations and previous results. For SDSS J0349-0059, we found a seismological model that provides us with additional information on the star.